2012
DOI: 10.1038/onc.2012.551
|View full text |Cite
|
Sign up to set email alerts
|

Cbl-independent degradation of Met: ways to avoid agonism of bivalent Met-targeting antibody

Abstract: The Met receptor tyrosine kinase, found to be constitutively activated in many tumors, has become a leading target for cancer therapy. Disruptions in Met downregulation have been associated with aggressive tumor progression with several therapeutic strategies addressing this aspect of Met biology. Castias B-lineage lymphoma (Cbl) E3 ligase-mediated degradation, which attenuates Met signaling via ligand-dependent Met internalization, is a major negative regulator of Met expression. It is believed that one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 42 publications
1
73
0
Order By: Relevance
“…However, subsequent studies from our group revealed that Cbl knockdown had no effect on Lrig1 activity toward the Met receptor (4), calling into question the role of Cbl and, by extension, the Lrig1 cytoplasmic domain in Lrig1 action. In agreement with our results, Lee et al (25) recently reported that the Met-targeting antibody SAIT301 promotes an Lrig1-dependent but c-Cbl-independent lysosomal degradation of the Met receptor. Our current results with ⌬-Cyto-Lrig1 demonstrate unequivocally that the cytoplasmic domain of Lrig1 is not required for the following: (a) complex formation with Lrig3 and (b) Lrig3 suppression, revising the model of Lrig1 function.…”
Section: Cross-talk Between Lrig1 and Lrig3supporting
confidence: 83%
“…However, subsequent studies from our group revealed that Cbl knockdown had no effect on Lrig1 activity toward the Met receptor (4), calling into question the role of Cbl and, by extension, the Lrig1 cytoplasmic domain in Lrig1 action. In agreement with our results, Lee et al (25) recently reported that the Met-targeting antibody SAIT301 promotes an Lrig1-dependent but c-Cbl-independent lysosomal degradation of the Met receptor. Our current results with ⌬-Cyto-Lrig1 demonstrate unequivocally that the cytoplasmic domain of Lrig1 is not required for the following: (a) complex formation with Lrig3 and (b) Lrig3 suppression, revising the model of Lrig1 function.…”
Section: Cross-talk Between Lrig1 and Lrig3supporting
confidence: 83%
“…However, HGF induced an IC 50 increase ranging from 5 to 24 times (Supplementary Table S1), a change that is in line with the IC 50 shifts induced by multiple rescuing cytokines in a recent major study on targeted drug resistance (23). In the case of antagonistic antibodies that reduce MET expression by inducing "shedding" or internalization (6,36,37), the mechanism responsible for HGF-induced rescue may rely on the fact that expression of MET in c-MET-amplified cells is way above the physiologic level, and antagonistic antibodies decrease MET expression down to normal levels rather than abrogating it (Fig. 4).…”
Section: Discussionmentioning
confidence: 52%
“…These MET ex14 alterations were shown to promote RNA-splicingbased skipping of MET exon 14, which results in activation of MET kinase activity through a unique mechanism. The portion of the protein encoded by exon 14, most prominently Y1003 in a DpYR motif, is required for effi cient recruitment of the ubiquitin ligase CBL, which targets MET for ubiquitinmediated degradation (16)(17)(18). Loss of MET exon 14 maintains the reading frame and leads to increased MET stability and prolonged signaling upon HGF stimulation, leading to increased oncogenic potential ( 19,20 ).…”
Section: Introductionmentioning
confidence: 99%